2016
DOI: 10.1016/j.bbalip.2016.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal protein S6 kinase1 coordinates with TOR-Raptor2 to regulate thylakoid membrane biosynthesis in rice

Abstract: Ribosomal protein S6 kinase (S6K) functions as a key component in the target of rapamycin (TOR) pathway involved in multiple processes in eukaryotes. The role and regulation of TOR-S6K in lipid metabolism remained unknown in plants. Here we provide genetic and pharmacological evidence that TOR-Raptor2-S6K1 is important for thylakoid galactolipid biosynthesis and thylakoid grana modeling in rice (Oryza sativa L.). Genetic suppression of S6K1 caused pale yellow-green leaves, defective thylakoid grana architectur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 60 publications
3
33
1
Order By: Relevance
“…Lipid content was referenced with deacylated anionic phospholipids used as standards. Other glycerolipids were extracted and analysed as described previously (Gao et al, ; Sun et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Lipid content was referenced with deacylated anionic phospholipids used as standards. Other glycerolipids were extracted and analysed as described previously (Gao et al, ; Sun et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…First-strand cDNA was produced from the RNA template by reverse transcription using the TIANscript RT Kit according to the manufacturer’s instructions (TransGen Biotech, Beijing). Quantitative real-time PCR was performed as described previously 50 . The primers for SQD2.2 were 5′-GCCGTGTTCACTGGAATGATGCAA-3′ (forward) and 5′-ATATCAGGAACACCACCAGCACGA-3′ (reverse).…”
Section: Methodsmentioning
confidence: 99%
“…The resultant lipids were separated on TLC plates using the developing solvent (acetone: toluene: H 2 O = 91:30:7.5, v/v) and were visualized with iodine vapor. The spot corresponding to SQDG was scraped out and was methylated with methanol containing 1% H 2 SO 4 and 0.05% BHT at 70 °C for 1 h. The SQDG was quantified according to the methods described previously 50 .…”
Section: Methodsmentioning
confidence: 99%
“…Recent reports involving TOR inhibitor treatment have indicated that these effects could be due to transcriptional downregulation of genes encoding plastidic ribosomal proteins and photosynthetic proteins as well as those of the tetrapyrrole biosynthesis pathway in Arabidopsis (Dobrenel, Mancera‐Martínez, et al, ; Dong et al, ). Thus, the TORC1 complex has been shown to play a crucial role in biogenesis and maturation of chloroplast to promote leaf and cotyledon greening (Li, Gao, Xue, Wang, & Zhao, ; Li, Song, et al, ; Mohammed et al, ; Sun et al, ; Zhang et al, ). Moreover, reports have also indicated that TOR kinase plays an important role in phytohormone signaling including that of auxin, gibberellic acid, brassinosteroids, and cytokinins etc (Li & Sheen, ; Quilichini et al, ; Wang et al, ; Wu et al, ; Xiong et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%